2011
DOI: 10.1177/0363546511424134
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Tendon Regeneration on MRI, Flexor Strength, and Functional Performance After Anterior Cruciate Ligament Reconstruction With Hamstring Autograft

Abstract: Hamstring tendons regenerated after harvest for ACL reconstruction in a high proportion of the patients. The flexor strength with both the standard and prone position isokinetic tests differed in the 3 groups. The number of regenerated hamstring tendons was significantly correlated with performance on the carioca test. Proximal shifting of the musculotendinous junction was significantly correlated with flexor deficit on the hyperflexion isokinetic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 46 publications
3
85
0
3
Order By: Relevance
“…These tendons provide good stability and strength [13], with evidence on MRI scans of tendon regeneration and almost normal insertion point on the pes anserinum six years after surgery. When comparing the operated and contralateral sides, even though cross sectional areas are similar, some strength deficits may persist, but the actual clinical impact of this is unknown [17]. On the other hand, the contralateral patellar tendon was not used to avoid the risk of patellar bone fracture and patellar tendon rupture [18].…”
Section: Discussionmentioning
confidence: 99%
“…These tendons provide good stability and strength [13], with evidence on MRI scans of tendon regeneration and almost normal insertion point on the pes anserinum six years after surgery. When comparing the operated and contralateral sides, even though cross sectional areas are similar, some strength deficits may persist, but the actual clinical impact of this is unknown [17]. On the other hand, the contralateral patellar tendon was not used to avoid the risk of patellar bone fracture and patellar tendon rupture [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nomura and colleagues (2014) showed that the length and volume of ST were 3.5 cm shorter and 26 % lower, respectively, in the ACLR limb compared to the uninjured contralateral limb in a group of recreationally active athletes. These results are similar to earlier studies (Choi et al, 2012;Simonian et al, 1996). It appears other knee flexor muscles do not compensate for ST muscle atrophy and this may contribute to greater deficits in hamstring strength following surgery (Nomura et al, 2015).…”
Section: Hamstring Graftssupporting
confidence: 94%
“…This persistent shortening of the ST/G muscles in regenerated tendons was further confi rmed in 2011 by Choi et al [ 5 ]. They reported that the musculotendinous junction shifted proximally by approximately 4 cm for the ST tendon and 3 cm for the G tendon resulting in signifi cant weakness in deep knee fl exion, minimum 2 years after surgery.…”
Section: Loss Of Strength and Morbidity Following Harvest Of The Tendonsmentioning
confidence: 68%
“…Another contributing factor to the inconsistency in the reported regeneration rate and insertion place could be differences in the harvesting procedure. Choi et al [ 5 ] who performed MRI [ 2 ]) have reported that 95 % of the tendons regenerated after harvest of both the ST and G . Axial MRI of the operated right side demonstrates how the measurements were done.…”
Section: What the Diagnostic Methods Have Shown: The Regeneration Ratmentioning
confidence: 99%